Acesso às políticas públicas sociais de mulheres do campo: uma análise da atuação da associação de mulheres trabalhadoras rurais do município de Belterra – Pará - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2019)
In Brazil, the first public policies for women were the result of the strengthening of social movements, which also corroborated the participation of women in the drafting of the constitutional text of 1988, which includes social rights for women. This study promotes a debate on social rights and public policies directed at rural women in the context of a rural association in the Amazon. The research addressed the following problem: What public policies does the Association of Rural Women Workers of the Municipality of Belterra-Pará (Amabela) have access to? Its general objective was to analyze the public policies that Amabela women have access to. This is a descriptive research, with a bibliographic survey (theoretical study) and semi-structured interviews (field research), with a qualitative approach, and the data were analyzed using the content analysis technique. Twenty associates were interviewed, which showed that Amabela women have access to general public policies focused on education, work and social security, and no specific public policy was reported for the associates. It was concluded that the association makes the women's movement stronger, despite having insufficient access to public policies. Being associated enables these women to have knowledge of their rights and guidance on how to claim them.
Keywords: Direitos sociais; Organização Social; Gênero; Amazônia